Evaluation of Antioxidant Activities of Methanolic Extract Leaves of Punica Granatum Linn. - Abdullahi Ishaq; Uwais Aminu; BakiBillah, Abul Hasan (Health Nexus, 2023)
Pomegranate (Punica granatum L.), an edible fruit native to Persia that is cultivated and consumed worldwide, including in Iran, has been esteemed throughout history for its medicinal properties. Pomegranate leaves serve as a valuable source of potentially beneficial bioactive compounds. This study aimed to explore the in vitro antioxidant properties of the methanolic extract obtained from Pomegranate leaves (Punica granatum L.) using the DPPH radical scavenging assay. The assessment of antioxidant activity in Punica granatum L. leaves demonstrated that the methanolic extract exhibited a promising IC50 value of 120.345 μg/ml, in comparison to the reference standard ASA, which had an IC50 of 90.545 μg/ml in the DPPH assay. These significant biological activities suggest that P. granatum leaves could potentially serve as a source of active compounds with applications in the pharmaceutical industry, contingent upon further in vivo experiments.